Amorphous GaN matrix embedded nanocrystals exhibiting bulk bandgap luminescence - Lakshman Srinivasan; Jean-Luc Maurice; Stefano Pirotta; Stéphane Collin; Erik V. Johnson; Pere Roca i Cabarrocas; Karim Ouaras (APL Materials, 2025)
This work reports on the room temperature sputtering growth of gallium nitride thin films, exhibiting band edge luminescence without thermal annealing or post-deposition processing. In particular, we investigate and correlate their luminescence spectra with their structural properties (amorphous or polycrystalline phases), the presence of defects, and the grain features by combining cathodoluminescence and HR-TEM characterizations. The working pressure and Ar/N2 flow ratio are found to have a profound effect on both the structural and optical properties of the films. Notably, the only film with band edge luminescence is grown at the highest investigated pressure (13.3 Pa) and 40% N2 concentration and exhibits single-grained crystallites of small sizes (∼5 nm). Moreover, this polycrystalline film has an almost equal fraction of amorphous and crystalline phases. This suggests that the presence of smooth and nanometer-sized crystals in an amorphous matrix (inducing grain surface passivation) could be a synergetic combination to achieve luminescent films grown at room temperature.